Dampak Kecerdasan Emosional, Efikasi Diri, Komitmen Organisasi Terhadap Performa Kinerja Mediasi Kreativitas Karyawan - Wike Gunawan; Justine Tanuwijaya; B Medina Nilasari (Jurnal Manajemen dan Organisasi, 2026)
This study aims to analyze the influence of emotional intelligence, self-efficacy, and organizational commitment on employee performance with employee creativity as a mediating variable at PT Toba Pulp Lestari Tbk. This study also aims to explain the mechanism by which individual psychological factors and organizational resources translate into work performance in the context of the pulp and paper industry, which is characterized by capital-intensive, labor-intensive, and efficiency-oriented with strict operational standards. The study used a quantitative approach with a cross-sectional survey design. Primary data were obtained through the distribution of online questionnaires to 61 employees who met the research criteria using a purposive sampling technique. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the direct and indirect relationships between variables. The results showed that emotional intelligence had a positive and significant effect on employee performance and creativity. Self-efficacy also had a positive and significant effect on employee creativity. Meanwhile, organizational commitment did not have a direct effect on employee creativity or performance. However, organizational commitment was shown to have an indirect effect on creativity through self-efficacy, and influenced performance through sequential mediation of employee self-efficacy and creativity. The study's conclusions confirm that individual psychological factors play a more dominant role than organizational attachment in driving creativity and performance in manufacturing industries with high levels of operational pressure. This study contributes to scientific research by extending the integration of Resource-Based View (RBV) and Social Cognitive Theory (SCT), explaining that an organization's intangible resources will only generate strategic performance capabilities if converted through employee self-efficacy and creative behavior. These findings reinforce the perspective that employee creativity is a key transformation mechanism linking psychological resources to organizational performance excellence in the context of heavy manufacturing industries.